ANALYZING THE EFFECTIVENESS OF TAX POLICIES IN IMPROVING A COMPANY'S FINANCIAL PERFORMANCE INVOLVES ASSESSING HOW TAXATION STRATEGIES IMPACT THE OVERALL ECONOMIC HEALTH OF THE BUSINESS - Loso Judijanto; Eko Sudarmanto; Ahmad Rizani; Andree Tiono Kurniawan; Ignatius Septo Pramesworo (CV. Adiba Aisha Amira, 2025)
This research engages in a thorough retrospective analysis to assess the historical effectiveness of tax policies in shaping the financial performance of companies. Through meticulous exploration of diverse taxation strategies employed over an extended temporal horizon, the study delves into the intricate dynamics that directly influence the overall economic health of businesses. The research reveals nuanced patterns and correlations by parsing through financial data and scrutinizing economic indicators, offering a rich understanding of the complex relationship between taxation strategies and fiscal well-being. Findings from this retrospective analysis contribute significantly to the ongoing discourse on the pivotal role of tax policies in corporate financial landscapes. The study unveils historical trends and establishes a robust foundation for informed considerations in future tax policy formulation and strategic financial planning. The keywords guiding this research—Tax Policies, Financial Performance, Taxation Strategies, Economic Health, and Fiscal Well-being—provide a comprehensive framework for exploring the multifaceted aspects of tax policy effectiveness, transcending temporal boundaries. This retrospective exploration is not confined to a specific era but spans diverse temporal contexts, offering insights that inform future financial strategies. The research serves as a valuable resource for policymakers, businesses, and academics alike, providing nuanced perspectives on the evolving nature of tax policies and their enduring impact on the financial trajectories of companies. The insights gleaned from this study underscore the imperative for adaptive financial strategies that navigate the dynamic interplay between taxation policies and corporate fiscal well-being.